Terlipressin Versus Norepinephrine for Septic Shock: A Systematic Review and Meta-Analysis - Huang, Po; Guo, Yuhong; Li, Bo; Liu, Qingquan (Frontiers in Pharmacology, 2019)
Purpose: The meta-analysis aims to evaluate the efficacy and safety of terlipressin compared with norepinephrine for septic shock. Materials and Methods: The relevant studies from MEDLINE, Cochrane Library, Embase were searched by two independent investigators. A variety of keywords were used to search the studies. Stata software (version 11.0, Stata Corp LP, College Station, TX, USA) was used for statistical analysis. Results: A total of six studies were identified and incorporated into the meta-analysis. The results showed that there was no difference for 28-day mortality (RR = 0.99, 95% CI = [0.85,1.15], P = 0.849), AE (RR = 2.54, 95% CI = [0.58,11.08], P = 0.214), and MAP (SMD = -0.10, 95% CI = [-0.35,0.14], P = 0.405), OI, urinary output, Scr, total bilirubin, ALT, and AST between TP group and NE group. While TP could decrease HR at 24 and 48 h compared with NE. Conclusions: Current results suggest that terlipressin showed no added survival benefit for septic shock when compared with norepinephrine, while terlipressin could decrease heart rate in the late phase of septic shock compared with norepinephrine without further liver and kidney injury. Systematic Review Registration: PROSPERO (ID: CRD42019128743). Available online at: http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42019128743.